QUESTIONING WEB 2.0 PRACTICES IN LANGUAGE LEARNING - Ozgur, Elmaziye; Kufi, Eren (Iated-Int Assoc Technology Education & Development, 2017)
With the developments in technology and education, educators have been trying to make use of Web 2.0 within the social-constructivist framework in order to turn their teaching into a more dynamic collaborative process and encourage their learners to be more active in knowledge construction. Similarly, language teachers benefit from Web 2.0 tools to cater for the needs and demands of their learners but the question is: Are these tools exploited to their full potential or are they simply used to create another form of traditional teaching, where classroom work is just repeated in an online medium? Triggered by this question, the present study aimed to explore practices with Web 2.0 in a division of a language school at a university in Northern Cyprus. To this end, the study first elicited perceptions of 200 students who have experienced the use of Web 2.0 in their English lessons through a questionnaire. As the preliminary data analysis revealed conflicting results with the social constructivist paradigm, the study employed a further investigation on how virtual learning environments are integrated into the English courses and the types of activities employed by the teachers in the research context. This paper, providing a thorough review of literature and experiences in the research context, discusses the need for questioning practices with Web 2.0 in language learning contexts and concludes that unless teachers critically reflect on their practices with Web 2.0, it will not be possible to use Web 2.0 tools effectively and to implement the principles of the social constructivist paradigm in English language lessons.
10th Annual International Conference of Education, Research and Innovation (ICERI) -- NOV 16-18, 2017 -- Seville, SPAIN
Keywords: Computer Mediated Communication; Web 2.0; Language learning; Language teaching practices